Perceived Appropriateness of Training and Organizational Commitment Among Korean Police - Baek, Hyunin (International criminal justice review, 2020)
Although organizational commitment (OC) generates several beneficial outcomes to law enforcement agencies, the policing literature has underexamined OC. Using data gathered from 11,709 Korean police in 2012, this study conducted analyses of structural equation modeling (SEM) in order to examine the relationship between OC and perceived organizational support. In addition, SEM was conducted to determine whether Allen and Meyer’s three components of OC is appropriate. The results indicated that two predictors of perceived appropriateness of training (i.e., perceived support of training and training needs) strongly accounted for OC. However, unlike previous studies, this study found that hypotheses in the model with the subcomponents of OC (affective, continuous, and normative commitments) could not be verified. In sum, for sturdier examinations, future studies should apply the Allen and Meyer model to diverse agencies.